Phenylisoxazole-3/5-Carbaldehyde Isonicotinylhydrazone Derivatives: Synthesis, Characterization, and Antitubercular Activity - Carrasco Solís, Fernando Carlos (2021)
Eight new phenylisoxazole isoniazid derivatives, 3-(2'-fluorophenyl)isoxazole-5-carbaldehyde isonicotinylhydrazone (1), 3-(2'-methoxyphenyl)isoxazole-5-carbaldehyde isonicotinylhydrazone (2), 3-(2'-chlorophenyl)isoxazole-5-carbaldehyde isonicotinylhydrazone (3), 3-(3'-clorophenyl)isoxazole-5-carbaldehyde isonicotinylhydrazone (4), 3-(4'-bromophenyl)isoxazole-5-carbaldehyde isonicotinylhydrazone (5), 5-(4'-methoxiphenyl)isoxazole-3-carbaldehyde isonicotinylhydrazone (6), 5-(4'-methylphenyl)isoxazole-3-carbaldehyde isonicotinylhydrazone (7), and 5-(4'-clorophenyl)isoxazole-3-carbaldehyde isonicotinylhydrazone (8), have been synthesized and characterized by FT-IR, 1H-NMR, 13C-NMR, and mass spectral data. The 2D NMR (1H-1H NOESY) analysis of 1 and 2 confirmed that these compounds in acetone-d6 are in the trans(E) isomeric form. This evidence is supported by computational calculations which were performed for compounds 1–8, using DFT/B3LYP level with the 6-311++G(d,p) basis set. The in vitro antituberculous activity of all the synthesized compounds was determined against the Mycobacterium tuberculosis standard strains: sensitive H37Rv (ATCC-27294) and resistant TB DM97. All the compounds exhibited moderate bioactivity (MIC¿=¿0.34–0.41¿µM) with respect to the isoniazid drug (MIC¿=¿0.91¿µM) against the H37Rv sensitive strain. Compounds 6 (X¿=¿4'-OCH3) and 7 (X¿=¿4'-CH3) with MIC values of 12.41 and 13.06¿µM, respectively, were about two times more cytotoxic, compared with isoniazid, against the resistant strain TB DM97.